GAMIFICATION AND THE CHALLENGES OF DIGITALISATION ON EMPLOYEE ENGAGEMENT, THE CASE OF ACADEMICIANS IN PRIVATE HIGHER EDUCATION INSTITUTIONS (PHEIS) KLANG VALLEY, SELANGOR. - Christina Rathy (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The focus of this paper is on Private Higher Education Institutions (PHEIs) in Klang Valley, Selangor, which also analyses digital receptivity, digital culture, employee engagement, and the digital revolution. The education sector has undeniably undergone a vigorous digital transformation and modernization. This has improved students’ learning experience by making the delivery of the syllabus more sophisticated and engaging. The effects of digitalization and employee engagement on the academicians have received less attention than the effects of digitalization and modernization on pedagogies. Researchers have shown that faculty members act as "gatekeepers" to workplace engagement, which in turn affects employees’ levels of enthusiasm, commitment, and focus. Two areas of unfilled research are the focus of this study. Firstly, this thesis examines the gap in the lack of research on the role digitalisation and employee engagement in PHEI among academicians. Secondly, to examine the digitalisation transition involving the gatekeepers. The result of this study underpins a possible solution for enhancing task characteristics (psychological meaningfulness), management style and process (psychological safety), and insecurity (psychological availability). The researcher examines the academics’ attitudes about digital technology between gamification, and employee engagement. Despite the large number of studies done to prove the link between the factors, it has become clear that most of these studies were carried out in non-Western settings. To rephrase, further research into the correlation between digitalisation and employee participation in specific regional contexts is required. To understand the lack of research addressed between digitalisation and employee engagement in PHEI among academics, and to evaluate the transition of digitalisation with gamification, it is necessary to undertake this study. The working hypothesis and conceptual framework for this inquiry have been formed via careful examination of the literature and ideas. Survey results will be evaluated for potential future relevance using partial least square-structural equation modeling (PLS-SEM) methods. Attempting to fill up the gaps in gamification evaluation, measurement, comparison, and construction, this paper stands out.